Una tierra más amable que el hogar - Cash, Wiley (Nuevos tiempos (Madrid, Spain), 2014)
Jess Hall, growing up deep in the heart of an unassuming mountain town that believes in protecting its own, is plunged into an adulthood for which he is not prepared when his autistic older brother, Stump, sneaks a look at something he isn't supposed to, which has catastrophic repercussions.